Dual-Comb Photoacoustic Spectroscopy of a Polymer Film - Friedlein, J. T.; Baumann, E.; Briggman, K. A.; Colacion, G. M.; Giorgetta, F. R.; Herman, D.; Hoenig, E. V.; Hwang, J.; Newbury, N. R.; Perez, E. F.; Yung, C. S.; Coddington, I.; et al. (2020 Conference on Lasers and Electro-Optics (CLEO), 2020)
Dual-comb photoacoustic spectroscopy (DCPAS) is a new spectroscopy technique that measures photoacoustic signals in thousands of wavelength bands simultaneously. We report the first demonstration of this technique and show DCPAS spectra of polymer films.